2021
DOI: 10.1111/jocs.15857
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of the scimitar syndrome

Abstract: Background and Aim: We sought to address the varied anatomical details, the diagnostic challenges, associated cardiopulmonary anomalies, the techniques, and outcomes of management, including re-interventions of scimitar syndrome.Methods: A total of 92 published investigations of scimitar syndrome were reviewed. Diagnostic information was provided by clinical presentations, radiographic findings, transthoracic and transesophageal echocardiography, computedtomographic angiography, magnetic resonance imaging, ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 86 publications
(1,033 reference statements)
0
23
0
Order By: Relevance
“…The aim of SS repair is to create an unrestricted new pathway for the SV without disturbing the systemic venous return. 1 Our method has several advantages compared to techniques previously reported. [2][3][4] The new pulmonary venous pathway is constructed behind the IVC, namely, outside of the heart.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The aim of SS repair is to create an unrestricted new pathway for the SV without disturbing the systemic venous return. 1 Our method has several advantages compared to techniques previously reported. [2][3][4] The new pulmonary venous pathway is constructed behind the IVC, namely, outside of the heart.…”
Section: Discussionmentioning
confidence: 95%
“…Various surgical techniques have been reported for its repair. 1 The most popular technique includes the direct reimplantation of the anomalous vein to the left atrium (LA) or the interatrial rerouting. However, these techniques are not applicable to all of the cases because of the heterogeneous anatomy of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…It warrants a multidisciplinary approach with input from interventional cardiology, pulmonary medicine, and cardiothoracic surgery. Treatment options include surgical repair of the anomalous pulmonary vein, transcatheter device closure of the shunt, medical management of PAH, or lung transplantation in refractory 5,6 The choice depends on anatomy, shunt size, severity of PAH, and presence of other comorbidities in the patient population.…”
Section: Discussionmentioning
confidence: 99%
“…As corroborated in our series, scimitar syndrome may belong to the cardiac malformations of the VACTERL association [ 19 ]. In general, surgical correction is recommended in all symptomatic patients and asymptomatic patients with pulmonary-to-systemic flow ratios greater than 1.5:1 or pulmonary-to-systemic flow ratios lesser than 1.5:1 in the settings of clinically treated pulmonary hypertension, stenosis of the scimitar vein, or concomitant cardiac lesions [ 18 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…A large European multi-center registry study showed that respiratory (including respiratory distress, recurrent upper respiratory tract infections, cyanosis, and pneumonia) as well as cardiac symptoms (including failure to thrive and congestive heart failure) occur in about 50% of all clinical cases [ 17 ]. An Indian study focusing on surgical outcomes in scimitar patients even showed that associated cardiac and extracardiac defects, particularly hypoplasia of the right lung, are present in up to three-quarters of cases, whereas operative mortality has been cited between 4.8% and 5.9% [ 18 ]. The aim of this study was to assess the spectrum of extra-cardiac anomalies and chromosomal anomalies, the intrauterine course, and the postnatal outcome of fetuses with scimitar syndrome.…”
Section: Introductionmentioning
confidence: 99%